2014
DOI: 10.1002/cam4.249
|View full text |Cite
|
Sign up to set email alerts
|

High CD49f expression is associated with osteosarcoma tumor progression: a study using patient‐derived primary cell cultures

Abstract: Overall prognosis for osteosarcoma (OS) is poor despite aggressive treatment options. Limited access to primary tumors, technical challenges in processing OS tissues, and the lack of well-characterized primary cell cultures has hindered our ability to fully understand the properties of OS tumor initiation and progression. In this study, we have isolated and characterized cell cultures derived from four central high-grade human OS samples. Furthermore, we used the cell cultures to study the role of CD49f in OS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…As a proof of concept we have confirmed expression of 7 proteins; two proteins confirm the origin of the hMSCs EVs (CD90 and CD81) [37] and five known proteins associated with tumor proliferation and anti-metastasis [38-42]. Proteomics data supports the notion that the protein sorting in the EVs is not a random event: a) the constancy between the proteomic assays on EVs preparations from two different donors.…”
Section: Discussionsupporting
confidence: 65%
“…As a proof of concept we have confirmed expression of 7 proteins; two proteins confirm the origin of the hMSCs EVs (CD90 and CD81) [37] and five known proteins associated with tumor proliferation and anti-metastasis [38-42]. Proteomics data supports the notion that the protein sorting in the EVs is not a random event: a) the constancy between the proteomic assays on EVs preparations from two different donors.…”
Section: Discussionsupporting
confidence: 65%
“…CD49f, which is also known as integrin α6, is found in adult stem cells [90]. Furthermore, CD49f plays an important role in the generation of some solid tumors, including osteosarcoma and hemangioma [91,92]. In CCA, Ding et al [62] reported that iCCA tissues exhibited higher expression of CD49f than non-tumor samples.…”
Section: Surface Markers Of Cancer Stem Cellsmentioning
confidence: 99%
“…However, no further study has been published to support the utility of CD117 in osteosarcoma. Previously, two independent groups have reported that CD49f may serve in osteosarcoma as another marker that can distinguish CSCs from the cells with limited tumorigenic capacity ( 14 ). Nevertheless, these two studies brought contradictory results.…”
Section: Introductionmentioning
confidence: 99%